2017
DOI: 10.1515/culture-2017-0050
|View full text |Cite
|
Sign up to set email alerts
|

This Pussy Grabs back: Humour, Digital Affects and Women’s Protest

Abstract: Abstract:The "affective" turn has enabled many scholars to theorise media representations not only as texts that can be distantly decoded but also as a matter of emotional attachments, intensities of feelings, synesthetic sensations, and embodied experiences. Yet, what has been less often theorized is how this affective meaningmaking is (re)shaped by the dynamic and interactive nature of social networking systems such as Facebook or Twitter. How do images and the affective qualities that "stick" to them, trave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…This article builds on our previous study (Bore et al, 2018), which examined the social media circulation of images from the 2017 Women's March. One of the key themes we identified was the prevalence of images featuring placards that mocked Trump's body.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This article builds on our previous study (Bore et al, 2018), which examined the social media circulation of images from the 2017 Women's March. One of the key themes we identified was the prevalence of images featuring placards that mocked Trump's body.…”
Section: Methodsmentioning
confidence: 99%
“…(Thorogood, 2016, p. 217)This so-called echo chamber phenomenon is often discussed in the context of social media. Critics argue that, rather than enabling debate and deliberative compromise essential for creating political change, our social media practices of “posting,” “liking” and “sharing,” along with algorithms, generate filter bubbles and echo chambers with restrictive partisan sentiments, where only like-minded people speak to each other (Bore et al., 2018; Jamieson & Capella, 2008; Pariser, 2012). Nevertheless, Bivens and Cole (2018, p. 6) maintain that “the prevalence of social media use, like Instagram, Facebook, and Twitter, provides a method through which individuals can push back against the legislative structures in the United States.” They illustrate in their work on “grotesque protest” that social media provides individuals with opportunities to resist attempts to control bodies and to reinsert individuals’ voices in political discourse that is aimed to exclude those bodies (Enli and Skogerbø, 2013).…”
Section: Literature Review: Offense Online Humor and Mediated Protestmentioning
confidence: 99%
See 1 more Smart Citation
“…The dominant strategy, here, is to ridicule Trump and/or his policies rather than appeal to a sense of social justice through emotions like anger or indignation. Various studies of the use of humour in resistance have found it to be a volatile strategy that both destabilizes one's own political project and that of the adversary (Holm, 2017;Kalviknes Bore et al, 2017;Rodrigues and Collinson, 1995). Thus, humour is often used to defuse the critical point one is making ('we were only joking') so as to circumvent retaliation while maintaining the critical potential of the utterance.…”
Section: Poking Fun At Powermentioning
confidence: 99%
“…, and studies on social protest (Bore et al 2017;Graefer et al 2019). Most studies, however, relate to political communication and journalism studies.…”
mentioning
confidence: 99%